2003
DOI: 10.1079/bjn2002766
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of garlic oil and fish oil on the hepatic antioxidant and drug-metabolizing enzymes of rats

Abstract: This present study was designed to investigate the combined modulatory effect of garlic oil (GO) and fish oil (FO) on the antioxidant and drug metabolism systems. Rats were fed either a low-maize oil (MO) diet (50 g MO/kg), high-MO diet (235 g MO/kg) or high-FO diet (205 g FO þ 30 g MO/kg) and received different doses of GO (0 -200 mg/kg body weight) three times per week for 6 weeks. Fatty acid analysis showed that 20 : 5n-3 and 22 : 6n-3 were incorporated into serum lipid at the expense of 18 : 2n-6 and 20 : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 45 publications
7
41
0
2
Order By: Relevance
“…These results are in agreement with many studies [44,45] who found that dietary supplement of garlic extract activated the antioxidant system and decreased peroxidation in aortic tissue in their experimental model. The water-soluble organo-sulfur compounds of garlic including S-allyl cysteine, S-allylmercaptocyteine, allicin, and selenium exhibited potent antioxidant and free radical scavenging activities in vitro and in vivo [46,47].…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with many studies [44,45] who found that dietary supplement of garlic extract activated the antioxidant system and decreased peroxidation in aortic tissue in their experimental model. The water-soluble organo-sulfur compounds of garlic including S-allyl cysteine, S-allylmercaptocyteine, allicin, and selenium exhibited potent antioxidant and free radical scavenging activities in vitro and in vivo [46,47].…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that SAC and SAMC possess high radical scavenging activity, which directly removes ROS (33,34). In addition to this direct effect, ABGE also increases the activity of antioxidant enzymes, so that excessive ROS is indirectly cleared (35). Consistent with our study, enhancement of the circulating levels of SOD and GSH-Px were observed following administration of garlic extract in the circulation of tumor-bearing animals.…”
Section: Discussionsupporting
confidence: 80%
“…Fish oil influenced the activity of hepatic CYP450 (Valdes et al, 1995;Chen et al, 2003), which might consequently influence the metabolism of estrogen. The lower status of n-3 long-chain fatty acids in vegetarians seems to be a good model to investigate the influence of DHA supplementation on estrogen metabolism.…”
Section: Estrogen Metabolitesmentioning
confidence: 99%
“…The oxidative metabolism of estrogen is catalyzed predominantly by hepatic cytochrome P450 (CYP450) (Huang et al, 1998;Yamazaki et al, 1998). Dietary fish oil increased the concentration of hepatic overall CYP450 and some subtypes of CYP450 in rats (Valdes et al, 1995;Chen et al, 2003). A preliminary study of Osborne et al (1998) indicated a decreased extent of 16a-hydroxylation of estradiol in women after supplemented with n-3 fatty acids.…”
Section: Introductionmentioning
confidence: 99%